(3cJGH JhMjOs - (3GdRfOGfj, YHO GdeLjO Hf YRjR,s 1942- (1985)
(3jJfGhd OdGdI hLhO Gddg HGdBjGJ GdehVMI aj Ndb Gddg hedchJg(B.s
(3aj (B: (3cJGH GdJhMjO(B. -(3W(B. 1. -(3LOI, GdSYhOjI (B: (3OGQ GdeLJeY, (B1985. -(3eL(B. 1.s
Keywords: (3Yde GdcdGes